Communication as a Factor Conditioning Effectiveness of Change Implementation on the Example of Sales Department of a Distribution Company - Maciej SCHAB; Marek DUDEK (Communications of International Proceedings, 2021)
Changing the business model across the organization is a time-consuming task and requires the involvement of all employees in the company. In such reality, the company should take care of efficient communication with employees with particular emphasis on feedback. Through feedback, it will become possible to shape the right attitudes of employees towards changes. The article presents the results of the survey of the opinions of sales department employees in a distribution company in relation to the organizational changes underway. The survey was commissioned by an enterprise that identified dysfunctions in communication with employees during organizational changes.
Keywords: Implementation Of Changes; Communication; Change Management.